Risk factors for heart, cerebrovascular, and kidney diseases: evaluation of potential side effects of medications to control hypertension, hyperglycemia, and hypercholesterolemia - Nawata, Kazumitsu (Frontiers in Cardiovascular Medicine, 2023)
Heart disease (HD), cerebrovascular disease (CBD), and kidney disease (KD) are serious diseases worldwide. These diseases constitute the leading causes of death worldwide and are costly to treat. An analysis of risk factors is necessary to prevent these diseases. Age and history of diseases were found to be very important factors, and the risk of having diseases could be almost doubled. Urine protein levels and recent large weight changes were also important factors for all three diseases and made the risks 10–30% higher, except for KD. For KD, the risk was more than double for individuals with high urine protein levels. Negative side effects were observed with antihypertensive, antihyperglycemic, and cholesterol medications. In particular, when antihypertensive medications were used, the risks were almost doubled for HD and CBD. The risk would be triple for KD when individuals were taking antihypertensive medications. If they did not take antihypertensive medications and took other medications, these values were lower (20–40% for HD, 50–70% for CBD, and 60–90% for KD). The interactions between the different types of medications were not very large. When antihypertensive and cholesterol medications were used simultaneously, the risk increased significantly in cases of HD and KD. It is very important for individuals with risk factors to improve their physical condition for the prevention of these diseases. Taking antihypertensive, antihyperglycemic, and cholesterol medications, especially antihypertensive medications, may be serious risk factors. Special care and additional studies are necessary to prescribe these medications, particularly antihypertensive medications.